2020
DOI: 10.2147/cmar.s260842
|View full text |Cite
|
Sign up to set email alerts
|

<p>Treatment of Gastric Cancer Patients During COVID-19 Pandemic: The West is More Vulnerable</p>

Abstract: The outbreak of the COVID-19 is currently the biggest international concern. Treatment of gastric cancer (GC) patients in the pandemic era with high hospital burden and under severe oncological/surgical resource constraints should implicate a need for resource reallocation with a new "pandemic" GC treatment algorithm. The neoadjuvant/perioperative (radio-)chemotherapy is applied in the majority of advanced GC cases with poor postoperative therapy compliance. In the East, radical surgery is frequently used in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…It is known that chemotherapy, like surgical interventions, has an immunosuppressive effect [14]. However, chemotherapy cannot be used at all in older adult patients, making surgery the only curative treatment option [15]. Our study established similar waiting times and neoadjuvant therapy rates in both study groups, suggesting that the COVID-19 pandemic has not delayed the surgical treatment of gastric cancer and not increased the tendency to neoadjuvant therapy.…”
Section: Discussionsupporting
confidence: 62%
“…It is known that chemotherapy, like surgical interventions, has an immunosuppressive effect [14]. However, chemotherapy cannot be used at all in older adult patients, making surgery the only curative treatment option [15]. Our study established similar waiting times and neoadjuvant therapy rates in both study groups, suggesting that the COVID-19 pandemic has not delayed the surgical treatment of gastric cancer and not increased the tendency to neoadjuvant therapy.…”
Section: Discussionsupporting
confidence: 62%
“…Particularly, considering the outcomes of two patients with rectal cancer who may also be evaluated for “watch & wait response”, it is obvious that deferring surgery leads to poor prognosis of these patients. Likewise, the same view can be shared regarding all cancers of GIS 12–14,16,27 . In a recent study by Kucejko et al, 28 it was found that patients with colon cancer who underwent surgery within 3–6 weeks from initial diagnosis had better 5‐year survival than the delayed ones.…”
Section: Discussionmentioning
confidence: 88%
“…If the treatment ends during the pandemic, it is controversial how to continue the treatment. However, considering the non-negligible risk of immunosuppression, surgery can be recommended to patients with a low risk [18]. In line with these recommendations, an increase was predicted in patients receiving neoadjuvant therapy, but it was observed that the rate of patients who received neoadjuvant therapy during the pandemic period decreased as the disease progressed to an advanced stage and they could not tolerate neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 97%